Initial clinical experience of intravenous tolvaptan sodium phosphate in patients with congestive heart failure. Issue 4 (April 2023) - Nakamura, Makiko; Imamura, Teruhiko; Wakakuri, Eri; Onoda, Hiroshi; Ushijima, Ryuichi; Kinugawa, Koichiro
Abstract: Tolvaptan sodium phosphate (Samtas®; Otsuka Pharmaceutical, Tokyo, Japan) is a newly available intravenous aquaretic diuretic (commercially available from May 2022), which acts as an arginine vasopressin V2 receptor antagonist. Thus far, optimal patient selection as well as safety and efficacy in real-world practice remain unknown. We experienced two patients with congestive heart failure treated with tolvaptan sodium phosphate. In one patient with right-sided heart failure, oral tolvaptan was converted to intravenous tolvaptan sodium phosphate, and another one with right and left-sided heart failure and impaired swallowing function received intravenous tolvaptan sodium phosphate on a de novo basis. Following the initiation of tolvaptan sodium phosphate, their congestive symptoms ameliorated immediately without any complications. Tolvaptan sodium phosphate may be safe and effective in real-world practice, although further studies are warranted to establish optimal patient selection and clinical management. Learning objective: We report here an initial experience of newly-introduced intravenous tolvaptan sodium phosphate in real-world practice. The novel medication might be particularly suitable for those with severe thirst, congestive gut edema, or requiring rapid amelioration of systemic/pulmonary congestion, although further accumulating experiences are warranted to establish optimal therapeutic strategy.